The Development of English Learning Video on Recount Text to Enhance Students’ Reading Comprehension Skill. - Syarifah Balqis Umamah aljufri; Ardiya Ardiya; Siti Niah (UIR Press, 2023)
In this age of technology, teachers must make learning materials exciting and beneficial to students. Some apps like Canva can help teachers create various English learning materials. Based on the researcher's observations, The researcher found several problems with students reading. This study aimed to investigate the development of an English learning video on recount text to improve the reading comprehension skills of tenth-grade students of SMA 5 Pekanbaru. The researcher used a model called Research and Development. The sampled class is grade X.7, The number of students in this study is 34. From the Researcher findings there was showed an improvement from the score of the t-test. The total score of the t-test was 33.42%. Based on the p-value was 0.000 < 0.05. Therefore, there was a development of applying video toward students reading comprehension of recount text at the tenth-grade students of SMA 5 Pekanbaru.